Assessment of Genetic Variability and Correlation of Yield Components of Elite Rice Genotypes (Oryza sativa L.) - Debsharma, SK; Disha, RF; Ahmed, MME; Khatun, M; Ibrahim, M; Aditya, TL (Bangladesh Rice Journal, 2021)
The study was conducted to evaluate the extent of variability among the elite rice (Oryza sativa L.) genotypes for yield and yield components. Sixteen elite rice genotypes were evaluated for yield and yield contributing characters in Bangladesh Rice Research Institute, Regional Station, Satkhira. Highest grain yield (t ha-1) was observed in BR(Bio)8333-BC5-2-16, which was followed by BR16, BRRI dhan28, BRRI dhan58 and BRRI dhan29. BR7671-37-2-2-37-3-P3 had the highest number of grains per panicle with minimum thousand grain weight. Correlation analysis revealed that the number of panicles per plant (0.301), days to 50% flowering (0.606) and grain yield per plant (0.393) had the significantly positive contribution to grain yield. After evaluation of yield components, four genotypes namely BR(Bio)8333-BC5-1-20, BR(Bio)8333-BC5-2-16, BR(Bio)8333- BC5-2-22 and BR(Bio)8333-BC5-3-10 were selected as outstanding genotypes, which can be used as potential breeding materials for variety development or in the crossing program to enrich the rice gene pool in Bangladesh. Bangladesh Rice J. 24 (1): 21-29, 2020